The Impact of Pandemic on Students’ Social Skills: Teachers’ Reflection towards English Speaking Class - Jovanda Febrianesty Ganiet; Joko Nurkamo; Sumardi Sumardi (Bina Nusantara University, 2023)
The research aimed to explore negative impact of the pandemic on students` social skills on speaking skill development. The shortcomings of a past pandemic era had impacted the offline English Foreign Learner (EFL) classroom in the new era. Dozen of difficulties and challenges that were faced by the students affected English speaking skills as one of the productive skills in language learning. As the core of English-speaking substances, online learning influenced the students’ social skills development, raising speaking anxiety due to the issue. The research was conducted applying a qualitative narrative method. Data were collected by interviewing three secondary teachers using semi-structured interviews, and the results were analyzed using Critical Discourse Analysis (CDA). The finding indicates that the pandemic has increased the students’ anxiety which has become a common factor that has been decreasing the students’ social skills; it is caused by the ineffective teaching procedure, learning media used, and activities that have been implied during the past pandemic era. Furthermore, despite that negative effect, this finding can be further developed to improve teaching methods in other emerging education conditions. In addition, an observation method is suggested to get the actual condition.